Does the clinical experience of a tutor influence how students learn extended focused assessment with sonography for trauma: A randomized controlled trial. (4th March 2023) - Szalai, Cynthia; Shehada, Sharaf-Eldin; Iancu, Simona; Herbstreit, Frank; Ruhparwar, Arjang; Brenner, Thorsten; Haddad, Ali
Abstract: Background: Extended focused assessment with sonography for trauma (eFAST) is now an essential part of the primary survey of an emergency patient. The discrepancy between an increasing number of medical students and growing clinical commitments of lecturers is a major challenge in student teaching that needs to be resolved. The practice of using peers in the clinical education of medical students is a well-established tradition and commonly practiced but lacks definition in its implementation. Therefore, we aimed to investigate whether the level of experience of the tutor affects the effectiveness of learning among students using eFAST during a clinical scenario. Methods: A prospective randomized single-blinded controlled trial, where 168 medical students in the eighth semester were randomized into control and intervention groups. The control group received the 4-h standard ultrasound (US) tutorial from various resident doctors. All residents were at least stage-1-certified in ultrasound. The intervention group received the tutorial from trained peer teachers (TPTs). These TPTs were medical students who were qualified to teach the procedure. All students received an initial tutorial on basic ultrasound principles and a final lecture on recognizing pathological images. Students completed basic questionnaires requesting pre-existing US experience, theoretical and clinical application questions based on eFAST one day later and at the end of the semester. Students also completed a 6-min OSCE (Objective-Structured-Clinical-Exam) station involving clinical emergency scenarios. Results: Eighty-five percent of participants had no previous eFAST experience. Early and later evaluation of the participants show no significant differences between both groups regarding the theoretical and the clinical application examinations, except the early phase OSCE results, which was not repeated in the late-stage results. Conclusions: Peer-teaching can be utilized to teach practical skills such as eFAST without a loss of clinical application skills. This relieves the burden of removing doctors from patient care situations and maintains teaching standards.